Epilepsy and Autoimmunity in Pediatric Patients - Bektaş, Ömer; Jacobson, Leslie; Tutkak, Hüseyin; Karagöl, Sema; Lang, Bethan; Clover, Linda; Vincent, Angela; Deda, Gülhis (Neuropediatrics, 2015)
Our aim was to determine the presence and possible role of autoantibodies in epileptic patients with an undetermined etiology. Eighty epilepsy patients, who were referred to the Pediatric Neurology Department at Ankara University between November 2011 and April 2012, were enrolled in the study. Antinuclear antibodies (ANA), anticardiolipin IgG, antiphospholipid, antithyroid peroxidase, paraneoplastic, glutamic acid decarboxylase (GAD), and N-methyl-d-aspartate (NMDA) receptor antibodies were studied in our university laboratory. In addition, NMDA receptor (NMDAR), voltage-gated potassium channel (VGKC)-complex, leucine-rich, glioma inactivated 1 (LGI1) and contactin-associated protein 2 (CASPR2) antibodies were studied at the Oxford University Immunology Laboratory. The study included 35 girls (44%) and 45 boys (56%) with a mean symptom age of 8.6 ± 4.53 years. ANA was detected in 15 (18.8%), antiphospholipid Ab in 3 (3.75%), anticardiolipin Ab in 1 (1.25%), and antithyroid peroxidase in 3 (3.75%) epileptic patients. In addition, anti-GAD Ab was detected in 7 (8.75%), anti-Yo Ab in 3 (3.75%), and anti-Ma2 in 3 (3.75%) epileptic patients. Anti-VGKC was positive in 13 (16.25%) epileptic patients. We performed a pioneer study to investigate the association between autoimmunity and pediatric epilepsy and we conclude that autoimmunity should be considered in epileptic patients with an undetermined etiology.
Keywords: epilepsy; autoimmune; pediatric; onconeural antibodies; VGKC antibodies